Disparities in use of physical restraint and chemical sedation in the emergency department by patient housing status - Leah Robinson; Caitlin R. Ryus; Bidisha Nath; Anusha Kumar; Riddhi Desai; Dhruvil Shah; Isaac V. Faustino; Ambrose H. Wong (PLoS ONE, 2025)
Background A growing body of research has found there to be disproportionate physical restraint and chemical sedation use for historically marginalized populations in the emergency department (ED). This association has been examined with regard to patient race, ethnicity, sex, and age. Preliminary research has highlighted the ways in which unhoused status may also relate to the use of physical restraint and chemical sedation in the ED. Given the adverse health outcomes associated with these methods in the ED, further research is needed to explore the relationship between patient housing status and physical restraint/chemical sedation use in more depth. Methods We conducted a cross-sectional study of all ED visits among patients aged 18 years of age and older presenting to eight hospitals within a regional healthcare network in New England between January 1, 2013, and December 31, 2021. Descriptive statistics and mixed effects logistic regression models nesting by patient were used to characterize the relationship between housing status and likelihood of restraint and/or sedation use. Findings Restraint orders were found in 3,160 (5.7%) visits by unhoused patients, compared to 44,155 (1.5%) for housed patients. Unhoused status was significantly associated with restraint/sedation use (adjusted odds ratio =  1.45, 95% CI 1.36-1.54). Conclusion Our study identified a significant association between housing status and ED restraint and sedation use after adjusting for demographic factors and chief complaints. This finding has important implications pertaining to the care of unhoused patients in the ED and for examination of structural factors like housing status and their impact on psychiatric emergency care.